2012
DOI: 10.1371/journal.pone.0050081
|View full text |Cite
|
Sign up to set email alerts
|

Generating Embryonic Stem Cells from the Inbred Mouse Strain DBA/2J, a Model of Glaucoma and Other Complex Diseases

Abstract: Mouse embryonic stem (ES) cells are derived from the inner cell mass of blastocyst stage embryos and are used primarily for the creation of genetically engineered strains through gene targeting. While some inbred strains of mice are permissive to the derivation of embryonic stem cell lines and are therefore easily engineered, others are nonpermissive or recalcitrant. Genetic engineering of recalcitrant strain backgrounds requires gene targeting in a permissive background followed by extensive backcrossing of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…Using this protocol, we have produced germline competent ES cell lines from a variety of mouse strains; including, those thought to be non-permissive, such as DBA 20 , PWD and NOD (our own unpublished data). Careful selection of healthy, blastocyst stage embryos, combined with minimal manipulations prior to plating promotes a high yield of ICM outgrowths from embryos that hatch naturally from the zona pellucida and adhere to MEF feeders.…”
Section: Anticipated Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using this protocol, we have produced germline competent ES cell lines from a variety of mouse strains; including, those thought to be non-permissive, such as DBA 20 , PWD and NOD (our own unpublished data). Careful selection of healthy, blastocyst stage embryos, combined with minimal manipulations prior to plating promotes a high yield of ICM outgrowths from embryos that hatch naturally from the zona pellucida and adhere to MEF feeders.…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…In incipient ES cell lines, we have found that serum-free 2i/LIF media (variant B) promotes robust NANOG expression and ultimately, higher yield of coat color chimeras through germline testing 20 . While serum-free culture conditions are typically employed in feeder-free culture systems, we have found that the use of feeders promotes more efficient derivation (# of embryos giving rise to ES cell lines / # embryos plated) and also yields a higher percentage of adherent ES cell lines, which are more favorable for gene targeting experiments.…”
Section: Anticipated Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…C1qa +/− mice. Endothelin deficient mice for assessment of the Edn2 riboprobes were obtained from our colony (Reinholdt et al , 2012). …”
Section: Methodsmentioning
confidence: 99%